A Study on Scale Base Approach of RBI on NBFCs Banking in India (Journal of Informatics Education and Research, 2025)
The Non-Banking Financial Companies (NBFC) sector in India has emerged as a crucial pillar of the country's financial system, offering a range of financial services that complement traditional banking. Over the past decade, NBFCs have grown rapidly in size and scope, contributing significantly to economic development, particularly in underserved regions and sectors. However, this rapid expansion has also introduced significant risks, including asset-liability mismatches, liquidity crises, and governance issues. In response to these challenges, the Reserve Bank of India (RBI) introduced the Scale-Based Regulation (SBR) framework in October 2021, a strategic regulatory approach designed to address the diverse nature and systemic importance of NBFCs. The SBR framework categorizes NBFCs into four layers—Base Layer (BL), Middle Layer (ML), Upper Layer (UL), and Top Layer (TL)—based on their size, activity, and risk profile, thereby enabling more tailored regulatory oversight.